The Role of Negative Emotions in the Social Processes of Entrepreneurship: Power Rituals and Shame‐Related Appeasement Behaviors. (22nd March 2013) - Doern, Rachel; Goss, David
<x xml:space="preserve">Abstract</x> This paper examines the role of negative emotions in the social processes of entrepreneurship. Drawing on a study of Russian entrepreneurs, we develop a model of the emotional effects of social interactions between entrepreneurs and state officials. We found that negative emotions were elicited by these interactions and, in turn, fueled three forms of shame‐related corrective appeasement behavior (reactive, anticipatory, and sporadic), which served to corrode entrepreneurial motivation and direct attention and energy away from business growth and development.